ТРИВИМІРНА МАТЕМАТИЧНА МОДЕЛЬ ТРИФАЗНОГО ТЕПЛОГЕНЕРАТОРА ІНДУКЦІЙНОГО ТИПУ З ВИКОРИСТАННЯМ МЕТОДУ ВТОРИННИХ ДЖЕРЕЛ - Жильцов, А.В.; Березюк, А.О.; Виштак, Т.В. (Інститут електродинаміки НАН України, Київ, 2022)
A three-dimensional mathematical model of a three-phase induction heat generator with a load in the form of a ferromagnetic conductive tubes beam has been developed on the basis of the secondary method. The magnetic system symmetry of the heat generator is taken into account, which significantly reduced the search area of unknown electromagnetic field secondary sources densities. References 5, figures 3.